Biomass responses in a temperate European grassland through 17 years of elevated CO2. (26th May 2017) - Andresen, Louise C.; Yuan, Naiming; Seibert, Ruben; Moser, Gerald; Kammann, Claudia I.; Luterbacher, Jürg; Erbs, Martin; Müller, Christoph
Abstract: Future increase in atmospheric CO2 concentrations will potentially enhance grassland biomass production and shift the functional group composition with consequences for ecosystem functioning. In the "GiFACE" experiment (Giessen Free Air Carbon dioxide Enrichment), fertilized grassland plots were fumigated with elevated CO2 (eCO2 ) year‐round during daylight hours since 1998, at a level of +20% relative to ambient concentrations (in 1998, aCO2 was 364 ppm and eCO2 399 ppm; in 2014, aCO2 was 397 ppm and eCO2 518 ppm). Harvests were conducted twice annually through 23 years including 17 years with eCO2 (1998 to 2014). Biomass consisted of C3 grasses and forbs, with a small proportion of legumes. The total aboveground biomass (TAB) was significantly increased under eCO2 ( p  = .045 and .025, at first and second harvest). The dominant plant functional group grasses responded positively at the start, but for forbs, the effect of eCO2 started out as a negative response. The increase in TAB in response to eCO2 was approximately 15% during the period from 2006 to 2014, suggesting that there was no attenuation of eCO2 effects over time, tentatively a consequence of the fertilization management. Biomass and soil moisture responses were closely linked. The soil moisture surplus (c. 3%) in eCO2 manifested in the latter years was associated with a positive biomass response of both functional groups. The direction of the biomass response of the functional group forbs changed over the experimental duration, intensified by extreme weather conditions, pointing to the need of long‐term field studies for obtaining reliable responses of perennial ecosystems to eCO2 and as a basis for model development. Abstract : Future increase of atmospheric CO2 concentrations will potentially enhance grassland biomass production with consequences for ecosystem functioning. In the "GiFACE" experiment (Giessen Free Air Carbon dioxide Enrichment), fertilized grassland plots were fumigated by air with elevated CO2 during 1998 to 2014. The total aboveground biomass was significantly increased under elevated CO2 by approximately 15 % during the late half of the time series, and was linked with only moderate increase in soil moisture. The dominant plant functional group grasses responded positively at the start, but for forbs the effect of elevated CO2 presented a negative response, as a result of climate extremes. Our long term study shows that the direction of the biomass response changed over the experimental duration, pointing to the need of long‐term field studies for obtaining reliable responses of perennial ecosystems to elevated CO2 .